COVID-19 vaccination in patients with cancer: Opportunities and challenges - Al-qaim, Zahraa Haleem; Owadh, Hasanain Kamil Hasan; Ali, Sarah A.; Hussein, Alaa S.; Ameen, Thamer Ramadhan; Kolemen, Ayshan; Washi, Ghassan A.; Jalil, Abduladheem Turki (Frontiers in Oncology, 2022)
Due to the rapid global spread of the SARS-Co-V-2 virus and the increasing number of people with serious and potentially fatal COVID-19 disease, there is an urgent need for safe and effective vaccines. Based on convincing evidence that cancer patients are at increased risk for Covid-19 disease and mortality. As a result, cancer patients have been prioritized for Covid-19 vaccination, both for primary vaccination and for booster vaccination. However, due to the fact that these patients did not undergo pivotal clinical trials, there is considerable ambiguity about the efficacy of the vaccine and the extent of humoral and cellular immune responses in these patients. The risks of vaccine-related side effects in cancer patients also remain unclear. In this commentary, we review existing data on the efficacy and safety of approved and future vaccines in cancer patients. We also highlight important points that may affect the effectiveness of the vaccine in future cancer patients. And we will discuss the opportunities and challenges associated with vaccinating cancer patients.